2016
DOI: 10.1155/2016/8519648
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MMP-3 and uPA with Diminished PAI-1 Related to Metastasis in Ductal Breast Cancer Patients Attending a Public Hospital in Mexico City

Abstract: Extracellular matrix metalloproteases and the fibrinolytic system are important protease systems interacting with each other in charge of remodeling and recycling of tissues. Their role in tumor invasion and metastasis is often discussed. In this study several metalloproteases such as MMP-1, MMP-3, MMP-9, and TIMP-1 together with molecules from the fibrinolytic system like uPA, its receptor uPAR, and its inhibitor, PAI-1, were studied by immune-histochemistry to establish a comparison with and without metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…MMP3 can degrade different collagens (such as types II, III, IV, IX, and X), proteoglycans, fibronectin, laminin, and elastin but can also activate MMP1, 7, and 9, proteins which play a crucial role in connective tissue remodeling [52,53]. Alterations in MMP3 expression and function are also involved in tumor metastasis [47,54,55]. In the current study, our bioinformatic analysis and luciferase reporter assay revealed that miR-134 was able to bind to the 3 0 -UTR of MMP1 and MMP3 and inhibited MMP1 and MMP3 translation or reduce MMP1/MMP3 message levels in osteosarcoma cells, which was correlated with the overexpression of miR-134 and inhibition of osteosarcoma cell migration, invasion, and metastasis in vitro and in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…MMP3 can degrade different collagens (such as types II, III, IV, IX, and X), proteoglycans, fibronectin, laminin, and elastin but can also activate MMP1, 7, and 9, proteins which play a crucial role in connective tissue remodeling [52,53]. Alterations in MMP3 expression and function are also involved in tumor metastasis [47,54,55]. In the current study, our bioinformatic analysis and luciferase reporter assay revealed that miR-134 was able to bind to the 3 0 -UTR of MMP1 and MMP3 and inhibited MMP1 and MMP3 translation or reduce MMP1/MMP3 message levels in osteosarcoma cells, which was correlated with the overexpression of miR-134 and inhibition of osteosarcoma cell migration, invasion, and metastasis in vitro and in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…uPA, a serine protease with multiple function, acts as risk assessment and a possible treatment target in many cancers, [10,17,18] such as breast cancer, [9,19,20] pancreatic cancer, [21,22] prostate cancer, [23,24] and ovarian cancer. [2527] In particular, uPA can accelerate tumor metastasis and promote tumor angiogenesis by degrading extracellular matrix (ECM) and basement membranes, such as vimentin and fibronectin, involving in epithelial-mesenchymal transition (EMT).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors exhibit the greatest metastatic activity when MMP expression is highest in all regions of the tumor (when MMP/TIMP ratio is highest in both tumor center and invasive front)[142]. MMPs, in general, can be found with high expression in many tumor surrounding cells, such as ECM cells, immune cells, fibroblasts, and endothelial cells[155]. This broad expression provides plenty of opportunities to use MMP-targeting techniques for the localization of therapeutic compounds within the immediate cancer cell vicinity.…”
Section: Matrix Metalloproteinases In Cancer: Why Are They Worthwhilementioning
confidence: 99%